"The lawless frontier" = [Frontera sin ley] - Bradbury, Robert N. (Robert North); Wayne, John, 1907-1979; Terry, Sheila; Lone Star Productions; Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1934)
John Tobin returns home after an absence of eight years. He has come to find Zanti, the outlaw who killed his parents. John teams up with an old gold miner and his grand-daughter, only to see their lives threatened by Zanti and his gang.
Originally released as a motion picture in 1934.
"A Paul Malvern production."
John Wayne, Sheila Terry, Jack Rockwell, George Hayes, Buffalo Bill, Jr., Yakima Canutt, Bud Wood, Earl Dwire.
Cinematographer, Archie Stout; editor, Charles Hunt; music
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Outlaws -- Drama; Adventure and adventurers -- Drama; Cowboys -- Drama; Western films; Feature films; Internet videos; Short films; Streaming video